DEVELOPMENT OF FOUR-TIER DIAGNOSTIC TESTS TO IDENTIFY MISCONCEPTION OF PARTICIPANTS IN WAVE AND OPTICAL MATERIALS - Andry Sutama Putra; Ida Hamidah; Nahadi Nahadi (Jurnal Pendidikan Fisika, 2019)
The study aims to develop a four-tier diagnostic test that can be used to identify students' misconceptions in wave and optical material. This research is developing research using the Plomp development model that was elaborated by the procedure for developing a four-tier diagnostic test by Pesman and Eryilmaz. The study was conducted in three junior high schools located in the Lembang sub-district in class VIII students. The instruments used were expert validation sheets, identification sheets of alternative concepts for students, and empirical validation instruments. Data analysis used is quantitative analysis by looking at the quality of the items. The results of the study showed that the content validity test obtained a CVI value of 0,848 which meant that the criteria were very suitable. The empirical validity test obtained the value of MNSQ outfit 1,00 and ZSTD outfit -0.0 which meant that it was included in the criteria of accepted values. While Point Measure Correlation, the whole item is included in the predetermined range. Item reliability is 0.93 and the alpha cronbach value of 0.85 also shows that the instrument developed has good reliability. The value of person Measure -0.29 < logit 0.0 indicates that the level of difficulty of the question includes a very good category. Overall, it can be concluded that the four-tier diagnostic test developed has met the criteria and is declared feasible to be used to identify students' misconceptions in wave and optical material